2015
DOI: 10.3389/fpsyg.2015.01529
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnocellular-based visual-motor intervention on Chinese children with developmental dyslexia

Abstract: Magnocellular (M) deficit theory points out that the core deficit of developmental dyslexia (DD) is the impairment in M pathway, which has been evidenced in many previous studies. Based on the M deficit, some researchers found that visual intervention focusing on M deficit improved dyslexics’ M function as well as reading abilities. However, the number and reliability of these training studies were limited. Therefore, the present study conducted an M-based visual-motor intervention on Chinese children with DD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…The digit cancelling task was a paper-and-pencil test 67 in which participants were required to search for a certain digit (a random integer between 0 and 9) rapidly in a 100-digit matrix (10 across by 10 down) within a time limit of 20 s (Fig. 6b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The digit cancelling task was a paper-and-pencil test 67 in which participants were required to search for a certain digit (a random integer between 0 and 9) rapidly in a 100-digit matrix (10 across by 10 down) within a time limit of 20 s (Fig. 6b).…”
Section: Methodsmentioning
confidence: 99%
“…The presentation format of each trial was consistent with the study by Lin et al . 67 . In each trial (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The interventions consisted of progressively more difficult coherent motion detection, visual search, visual tracking and juggling. These exercises improved magnocellular pathway function, and this was associated with significant increases in phonological awareness [ 42 ]. Likewise, Gori et al [ 43 ] showed that getting dyslexic children to play action video games with no reading or phonological content helped them to greatly improve both their visual magnocellular function and their reading.…”
Section: Visual Treatmentsmentioning
confidence: 99%
“…Previous studies have indicated that the visual perceptual processing (e.g., the low-spatial-frequency sensitivity, geometric-figure processing) had an impact on the recognition and encoding processes during Chinese reading in typically developed children and adults (Luo et al, 2013; Yang et al, 2013; Zhao et al, 2013, 2014). Various studies have shown that Chinese individuals with developmental dyslexia exhibit visual deficits (Chung et al, 2008; Wang et al, 2010; Meng et al, 2011; Qian and Bi, 2014), and visual function training for dyslexics can improve their reading-related skills (Meng et al, 2014; Wang et al, 2014; Qian and Bi, 2015). …”
Section: Introductionmentioning
confidence: 99%